Human microbiota drives hospital-associated antimicrobial resistance dissemination in the urban environment and mirrors patient case rates - Cecilia Salazar; Matias Giménez; Nadia Riera; Andrés Parada; Josefina Puig; Antonio Galiana; Fabio Grill; Mariela Vieytes; Christopher E. Mason; Verónica Antelo; Bruno D’Alessandro; Jimena Risso; et al. (Microbiome, 2022)
Abstract Background The microbial community composition of urban environments is primarily determined by human activity. The use of metagenomics to explore how microbial communities are shaped in a city provides a novel input that can improve decisions on public health measures, architectural design, and urban resilience. Of note, the sewage system in a city acts as a complex reservoir of bacteria, pharmaceuticals, and antimicrobial resistant (AMR) genes that can be an important source of epidemiological information. Hospital effluents are rich in patient-derived bacteria and can thus readily become a birthplace and hotspot reservoir for antibiotic resistant pathogens which are eventually incorporated into the environment. Yet, the scope to which nosocomial outbreaks impact the urban environment is still poorly understood. Results In this work, we extensively show that different urban waters from creeks, beaches, sewage spillways and collector pipes enclose discrete microbial communities that are characterized by a differential degree of contamination and admixture with human-derived bacteria. The abundance of human bacteria correlates with the abundance of AMR genes in the environment, with beta-lactamases being the top-contributing class to distinguish low vs. highly-impacted urban environments. Indeed, the abundance of beta-lactamase resistance and carbapenem resistance determinants in the urban environment significantly increased in a 1-year period. This was in line with a pronounced increase of nosocomial carbapenem-resistant infections reported during the same period that was mainly driven by an outbreak-causing, carbapenemase-producing Klebsiella pneumoniae (KPC) ST-11 strain. Genome-resolved metagenomics of urban waters before and after this outbreak, coupled with high-resolution whole-genome sequencing, confirmed the dissemination of the ST-11 strain and a novel KPC megaplasmid from the hospital to the urban environment. City-wide analysis showed that geospatial dissemination of the KPC megaplasmid in the urban environment inversely depended on the sewage system infrastructure. Conclusions We show how urban metagenomics and outbreak genomic surveillance can be coupled to generate relevant information for infection control, antibiotic stewardship, and pathogen epidemiology. Our results highlight the need to better characterize and understand how human-derived bacteria and antimicrobial resistance disseminate in the urban environment to incorporate this information in the development of effluent treatment infrastructure and public health policies. Video Abstract